ASSOCIATION OF TYPE 2 DIABETES MELLITUS AND CANDIDIASIS : A TEN YEARS SYSTEMATIC REVIEW - Yulianto, Ronald; Aristika Gunawan, Ellen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Diabetes mellitus is a chronic disease that may reduce resistance to microbial infection of tissues and decrease tissue repair capacity. It is both an endocrine and a metabolic dysfunction involving the control of blood glucose levels, resulting in hyperglycemia. The aim: The aim of this study to show about association of type 2 diabetes mellitus and candidiasis. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Diabetic patients had a higher candidal carriage rate and a variety of candidal species that were resistant to azole antifungal agents.